Psychological agency : evidence from the urban fringe of Bamako - Klein, E (2014)
There is a large deficit in the theorisation of psychological elements of agency and empowerment in the development literature. Instead, empowerment is generally defined as a favourable opportunity structure, as choice, or as the distribution of power. Further still, an examination of the psychological literature reveals a lack of empirical research related to non-Western contexts and development policy. In view of this, I present the results of an empirical study using inductive mixed methods to examine the central factors contributing to initiatives people undertake to improve personal and collective well-being. Informants articulated that the psychological concepts of dusu (internal motivation) and ka da I yèrè la (self-efficacy) were most important to their purposeful agency.